Parental Stress, Religious Coping and Dyadic Adjustment in Parents of Children with an Autism Spectrum Disorder - Sayed Reza Fallahchai; Arefeh Moazen Jami; Maryam Fallahi (Ravānshināsī-i Afrād-i Istis̠nāyī, 2017)
The aim of this study was to investigate the relationship between parental stress, religious coping and marital adjustment in the parents of autistic children. The sample consisted of 124 mothers and fathers with autistic children who were selected from the available population in Mashhad. Data were collected from demographic information questionnaire, short form of Parenting Stress Index, Religious Coping Activity Scales, and Marital Adjustment Scale that the validity and reliability of those were collected in Iran. A descriptive correlation design was employed in this study. For data analysis, Pearson correlation test and stepwise regression were utilized. The results showed that there is a positive relationship between parental stress and positive religious coping with marital adjustment, and there is a negative and significant relationship between negative religious coping with marital adjustment. Therefore, it seems that parental stress and religious coping variables are important and effective factors in the marital adjustment of autistic children's parents.